Učne oblike v osnovni šoli in obrnjeno učenje in poučevanje - Plešec Gasparič, Romina; Valenčič Zuljan, Milena (Revija za elementarno izobraževanje, 2019)
Within-class Pupil Grouping in Primary School and Flipped Learning and Teaching. There are many factors associated with effective instruction that should be taken into account by school policy, the school as an institution and each individual teacher. The teacher’s role is of utmost importance when it comes to factors influencing the didactic design of instruction, among which we focus on within-class pupil grouping. The paper presents a study that examined attitudes and experiences of Slovenian primary school teachers with planning, implementing and evaluating within-class pupil grouping. The results of teacher assessments of the effectiveness of each form of grouping show that teachers give the highest rating to individualised learning. Among the disadvantages of interactive grouping, teachers emphasize time consumption. Thus, we present the didactic innovation of flipped learning and teaching, which offers the opportunity for more frequent use of interactive grouping.Keywords: effective instruction, within-class pupil grouping, didactic innovation, flipped learning and teachingDOI: https://doi.org/10.18690/rei.12.3.267-290.2019COBISS-ID: 12626249